A decrease in blood pressure is associated with unfavorable outcome in patients undergoing thrombectomy under general anesthesia. (12th April 2017) - Treurniet, Kilian M; Berkhemer, Olvert A; Immink, Rogier V; Lingsma, Hester F; Ward-van der Stam, Vivian M C; Hollmann, Markus W; Vuyk, Jaap; van Zwam, Wim H; van der Lugt, Aad; van Oostenbrugge, Robert J; Dippel, Diederik W J; Coutinho, Jonathan M; et al.
Abstract : Background: Up to two-thirds of patients are either dependent or dead 3 months after thrombectomy for acute ischemic stroke (AIS). Loss of cerebral autoregulation may render patients with AIS vulnerable to decreases in mean arterial pressure (MAP). Objective: To determine whether a fall in MAP during intervention under general anesthesia (GA) affects functional outcome. Methods: This subgroup analysis included patients from the MR CLEAN trial treated with thrombectomy under GA. The investigated variables were the difference between MAP at baseline and average MAP during GA (ΔMAP) as well as the difference between baseline MAP and the lowest MAP during GA (ΔLMAP). Their association with a shift towards better outcome on the modified Rankin Scale (mRS) after 90 days was determined using ordinal logistic regression with adjustment for prognostic baseline variables. Results: Sixty of the 85 patients treated under GA in MR CLEAN had sufficient anesthetic information available for the analysis. A greater ΔMAP was associated with worse outcome (adjusted common OR (acOR) 0.95 per point mm Hg, 95% CI 0.92 to 0.99). An average MAP during GA 10 mm Hg lower than baseline MAP constituted a 1.67 times lower odds of a shift towards good outcome on the mRS. For ΔLMAP this association was not significant (acOR 0.97 per mm Hg, 95% CI 0.94 to 1.00, p=0.09). Conclusions: A decrease in MAP during intervention under GA compared with baseline is associated with worse outcome. Trial registration number: NTR1804 ; ISRCTN10888758 ; post-results.